The INFLUENCE OF INFLUENCER MARKETING AND BRAND AWARENESS ON PURCHASE DECISIONS OF KAHF SKINCARE PRODUCTS AMONG GENERATION Z - Rivandy, Radhinal A; Roza, Suswita; Hasbullah, Husni (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to analyze the influence of influencer marketing and brand awareness on the purchasing decisions of Kahf skincare products among Generation Z. The research is grounded in the rapid growth of the male skincare industry in Indonesia and the increasing role of social media and influencers as dominant digital marketing strategies. A quantitative approach was employed, using a structured questionnaire distributed to 100 Gen Z respondents in Jambi City who had purchased Kahf products and were exposed to influencer promotions. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) to examine the relationships among variables. The findings indicate that both influencer marketing and brand awareness have a positive and significant impact on purchasing decisions. The results suggest that trust, attractiveness, and brand presence in consumers' minds play critical roles in influencing buying behavior, particularly among digitally native consumers.